ANXIETY IN JOHN GREEN’S THE FAULT IN OUR STARS - Utari Onthoni; Olga Rorintulus; Imelda Lolowang (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This study aims to reveal what kinds of anxiety happen to Hazel. The causes of her anxiety can be seen first appear at the age of 13 when she was diagnosed of having a lung cancer, since then she is always thought about dying because the pain she felt rise her anxiety to die and it has a big impact toward people around her. Especially her parents and boyfriend cause she is worry that she will hurt people around. It is reflected in John Green’s The Fault In Our Stars. This research is classified as a qualitative research because the data gathered are in the form of words as the quotation that taken from the source. The writer collects the data from two kinds of sources. Primary source the novel itself and secondary sources is another references related to the novel like books and internet. The writer applied psychological approach because it is very close with human life such as feeling.The result of this research shows that there are 2 kinds of anxiety that appear, state anxiety and trait anxiety. State anxiety is one of anxiety that arise due to the dangerous situation. It can appear to Hazel as a cancer patient because she might be felt worry about the treatement and feel threatened. Meanwhile trait anxiety referes to anxiety as a characteristic of a person, so that person is generally anxious about unknown outcomes. Hazel seem to have trait anxiety in herself when she was overthinking about her dream.